Real world pharmacovigilance assessment of drug related macular degeneration risks - Xiaodong Chen; Shinan Wu; Shaopan Wang; Chaofeng Yu; Zihan Guo; Shiya Huang; Peixin Cai; Yanliang Miao; Shiying Li; Qian Chen (Scientific Reports)
Abstract Macular degeneration is a leading cause of irreversible vision loss, significantly impacting quality of life. To enhance clinical practice and reduce the risk of drug-related macular degeneration, we analyzed drug-related trends using real-world data. Disproportionality analysis of adverse event reports from the FDA Adverse Event Reporting System (FAERS, 2004–2023) identified 67,683 cases involving 1402 drugs. Among these, 42 drugs were linked to significant risks, including treatments for breast cancer (tamoxifen, raloxifene, anastrozole, letrozole) and diabetes (insulin lispro, insulin human). The BCPNN algorithm revealed that 45.2% (19/42) of these drugs had the strongest associations with macular degeneration, with pentosan polysulfate sodium, travoprost, and tolterodine being the highest-risk drugs. Lifitegrast, nicotine, and travoprost were associated with the shortest onset times for ocular adverse events. Among drug classes, glucocorticosteroids were linked to the most rapid onset of ocular side effects (P < 0.001), typically occurring within two months compared to other drugs. Drug-related macular degeneration was more common in women (70.4%) and predominantly affected those aged 60–80. The incidence of drug-related macular degeneration has steadily increased in recent years. This study offers valuable pharmacovigilance insights, highlighting drugs and demographic factors linked to macular degeneration.